Using Picture Story Media to Improve Reading Aloud Ability in Grade 4 Elementary School Students - septiani, putri reza; Uswatun, Din Azwar; Nurmeta, Irna Khaleda (JUPE : Jurnal Pendidikan Mandala, 2025)
This research aims to describe the use of picture story media to improve the ability to read aloud in grade 4 elementary school students. This research took place in grade 4 students at Nagrak 1 Elementary School in Nagrak District, Sukabumi Regency, West Java, consisting of 30 students. The research method used was classroom action research (PTK) Kemmis and Mc Taggart model research design which was carried out in two cycles. Each cycle consists of planning, implementation, action and observation, and reflection. Data collection techniques use practical reading aloud tests, and non-tests in the form of observation, field notes and documentation. The data analysis technique used is qualitative. Indicators for reading aloud consist of 1) pronunciation, 2) intonation, 3) reading speed, 4) pauses, 5) understanding of the material. Based on the comparative percentage of completeness of learning outcomes for each cycle, there is an increase in reading aloud skills after implementing picture story media, seen from the results of the percentage of completeness of students who meet the KKM (75) pre-cycle, namely 23% or 7 students, in the first cycle it is 57% or 17 students ,and cycle II amounted to 83% or 25 students. In the pre-cycle to cycle I there was an increase of 34.% and in cycle I to cycle II there was an increase of 26%, so providing action through these two cycles can improve students' ability to read aloud. Therefore, the application of picture story media succeeded in improving reading aloud skills and the research was stopped in cycle II based on predetermined success indicators.